Limitation standard of toxic aconitines in Aconitum proprietary Chinese medicines using on-line extraction electrospray ionization mass spectrometry - Zi-Dong Qiu; Xu-Ya Wei; Rui-Qi Sun; Jin-Long Chen; Ting Tan; Jia-Quan Xu; Guang-Hong Cui; Tong Chen; Juan Guo; Chang-; Lu-Qi Huang (Elsevier, 2020)
Development of rapid analytical methods and establishment of toxic component limitation standards are of great importance in quality control of traditional Chinese medicine. Herein, an on-line extraction electrospray ionization mass spectrometry (oEESI-MS) coupled with a novel whole process integral quantification strategy was developed and applied to direct determination of nine key aconitine-type alkaloids in 20 Aconitum proprietary Chinese medicines (APCMs). Multi-type dosage forms (e.g., tablets, capsules, pills, granules, and liquid preparation) of APCM could be determined directly with excellent versatility. The strategy has the characteristics of high throughput, good tolerance of matrix interference, small amount of sample (∼0.5 mg) and reagent (∼240 μL) consumption, and short analysis time for single sample (<15 min). The results were proved to be credible by high performance liquid chromatography−mass spectrometry (LC-MS) and electrospray ionization mass spectrometry, respectively. Moreover, the limitation standard for the toxic aconitines in 20 APCMs was established based on the holistic weight toxicity (HWT) evaluation and the Chinese Pharmacopoeia severally, and turned out that HWT-based toxicity evaluation results were closer to the real clinical applications. Hence, a more accurate and reliable APCM toxicity limitation was established and expected to play an important guiding role in clinics. The current study extended the power of ambient MS as a method for the direct quantification of molecules in complex samples, which is commonly required in pharmaceutical analysis, food safety control, public security, and many other disciplines.